COMPASS - Comparative Analysis of Territorial Governance and Spatial Planning Systems in Europe. Applied research 2016-2018. Final report. - (:unkn) unknown (My University, 2018)
The project compares territorial governance and spatial planning in 32 European countries (the 28 EU member states plus four ESPON partner countries). The Final Report contains an executive summary mainly based on the key policy questions; a short description of the methodology and conceptual framework; comparative analyses of the findings and policy recommendations; synthesis of the case studies, and case study reports; recommendations for future research and ongoing monitoring. This report contains annexes that are needed to understand the points made in the text. Additional volumes set out the data collected for the report and preliminary analysis.
Keywords: Raumplanung; Regionalplanung; Raumordnungspolitik; Internationaler Vergleich; Vergleichsanalyse; Mehrebenensystem